Peran Produser Dalam Pembuatan Program Feature Kuliner “Rasa Nusantara” Edisi Warung MJS - Anggrid Putri Dewi; Muhammad Darwinsyah (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
With the decreasing popularity of typical Indonesian food, television must develop more creativity in Indonesian culinary feature programs, therefore the role of television media is needed which can present information about culinary with interesting concepts and also present a variety of dishes from various regions in Indonesia. The creator of the work created a culinary feature program that has a lot of information and is also a reference for unique and interesting places to eat or restaurants with the theme of typical Indonesian food as inspiration and is also suitable for generation Z to get to know and preserve the culinary riches of the archipelago. The creator created a culinary feature program "Rasa Nusantara" Edisi Warung MJS. In the work on this culinary feature program, the creator as Producer is tasked with overall responsibility for the implementation of this production relating to audio visuals and is involved in creating or packaging a program concept or idea chosen in Pre-Production, Production and Post-Production. The general benefits include adding to the impressions of Indonesian culinary tourism and providing alternative entertainment for viewers of this program. The hope is that this culinary feature work will present information about Indonesian culinary locations in Jakarta, namely a feature show that has the unique characteristics of a place that is attractive to Generation Z and that the audience will also have the opportunity to enjoy this culinary program as entertainment.